Intestinal stem cells: no longer immortal but ever so clever … - Edgar, Bruce (The EMBO journal, 2012)
To maintain tissue homeostasis, stem cells must balance self‐renewal with differentiation. In some stem cell lineages this process is ‘hard‐wired’ by the asymmetric partitioning of determinants at division, such that one stem cell daughter always remains pluripotent and other differentiates. But in a dynamic tissue like the intestinal epithelium, which might need to repair itself following an infection or expand to digest the fall harvest, this balancing act requires more flexibility. Recent studies of intestinal stem cell (ISC) lineages in the fruit fly and mouse provide new insights into how this plasticity is achieved. The mechanisms in these two homologous but rather different organs have remarkable similarities, and so are likely relevant to how stem cell pools are controlled in organs other than the intestine.